Kreativitas, e-WOM, motif, dan kepemimpinan merek dalam membangun minat pembelian ulang: Peran mediasi emosi pada minuman kekinian di Kota Batam - Putra, Edy Yulianto; Angelina, Novi; Purwianti, Lily (Nur Science Institute, 2025)
Social media commerce has increasingly served as a primary platform for sharing product and service information, while also facilitating the buying and selling process. It has become a crucial source of information in consumer purchasing decisions. This study aims to examine the effects of stimuli, namely creativity, electronic word of mouth (E-WOM), motives, and brand leadership, on repurchase intention, with emotion acting as the mediating variable, among consumers of contemporary beverages in Batam City. Data were collected through a questionnaire distributed to 288 respondents and analyzed using the Structural Equation Modeling–Partial Least Squares (SEM-PLS) method. The findings indicate that creativity, E-WOM, and motives have a significant and positive influence on repurchase intention through emotional mediation. In contrast, brand leadership has no significant effect. This study contributes to a broader understanding of the role of social media in shaping consumer purchasing decisions in the contemporary beverage industry. The findings also provide strategic implications for business actors to focus on enhancing creativity, strengthening word-of-mouth communication on social media, and fostering emotional connections with consumers to encourage repeat purchases.